Integrating Waqf and Takaful: Developing the Inclusive Takaful Waqf Ecosystem (ITWE) in Indonesia - Sutrimo Sutrimo; Ucu Cahyana; Ahmad Subagyo (Journal of Indonesian Islamic Studies, 2026)
This study examines the development of waqf-based takaful products in Indonesia through the integration of an inclusive Islamic financial ecosystem. The research was motivated by the significant disparity between the enormous potential of national waqf assets and the limited utilization of takaful as a mechanism for protecting waqf properties from various risks. Employing a mixed methods approach with an explanatory sequential design, the study collected quantitative and qualitative data from key stakeholders in the Islamic insurance and waqf sectors, including sharia insurance companies, regulators, and waqf institutions. Data were analyzed using the Analytic Network Process integrated with Strengths, Weaknesses, Opportunities, and Threats (ANP-SWOT) analysis to identify strategic priorities and formulate an ecosystem-based development model. The findings reveal that regulatory support, the tabarru’ risk-sharing mechanism, and the increasing value of waqf assets constitute the most influential factors supporting the development of waqf-based takaful products. Conversely, the absence of dedicated waqf insurance products, limited institutional capacity, fragmented waqf data systems, and strong competition from conventional insurance providers remain significant challenges. Based on these findings, this study proposes the Inclusive Takaful Waqf Ecosystem (ITWE), an integrated framework that connects regulators, waqf institutions, takaful operators, religious authorities, donors, and beneficiaries within a collaborative financial ecosystem. The study contributes to the literature on Islamic financial ecosystems by demonstrating how Islamic social finance and Islamic commercial finance can be integrated to strengthen waqf asset protection, enhance Islamic financial inclusion, and support sustainable socio-economic development in Indonesia.